2019
DOI: 10.1175/bams-d-18-0181.1
|View full text |Cite
|
Sign up to set email alerts
|

POLSTRACC: Airborne Experiment for Studying the Polar Stratosphere in a Changing Climate with the High Altitude and Long Range Research Aircraft (HALO)

Abstract: The Polar Stratosphere in a Changing Climate (POLSTRACC) mission employed the German High Altitude and Long Range Research Aircraft (HALO). The payload comprised an innovative combination of remote sensing and in situ instruments. The in situ instruments provided high-resolution observations of cirrus and polar stratospheric clouds (PSCs), a large number of reactive and long-lived trace gases, and temperature at the aircraft level. Information above and underneath the aircraft level was achieved by remote sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 102 publications
0
14
1
Order By: Relevance
“…In contrast to these results, different mass budget analyses of the lowermost stratosphere in both hemispheres show that the net direction of the hemispherically integrated mass flux across the tropopause is downward with a maximum during spring in each hemisphere and a generally weaker seasonality in the SH. The upward component of this net mass flux is shown to reach its maximum during fall and its minimum conversely in spring in each hemisphere (Olsen et al, 2004;Schoeberl, 2004). The contradicting seasonality patterns imply that a hemispherically integrated mass flux might not be a suitable proxy for upward transport across the defined extratropical tropopause sections in this study, especially since the net direction of this flux is downward.…”
Section: Extratropical Seasonal Cyclesmentioning
confidence: 54%
See 2 more Smart Citations
“…In contrast to these results, different mass budget analyses of the lowermost stratosphere in both hemispheres show that the net direction of the hemispherically integrated mass flux across the tropopause is downward with a maximum during spring in each hemisphere and a generally weaker seasonality in the SH. The upward component of this net mass flux is shown to reach its maximum during fall and its minimum conversely in spring in each hemisphere (Olsen et al, 2004;Schoeberl, 2004). The contradicting seasonality patterns imply that a hemispherically integrated mass flux might not be a suitable proxy for upward transport across the defined extratropical tropopause sections in this study, especially since the net direction of this flux is downward.…”
Section: Extratropical Seasonal Cyclesmentioning
confidence: 54%
“…For the NH tropopause section, the net flux across the section is downward (Olsen et al, 2004), so that tropospheric air mixes with descending stratospheric air, characterized by lower mixing ratios due to the chemical loss regions in the stratosphere. At the extratropical tropopause the mixing ra-tio should thus be lower than in the tropics.…”
Section: Observational Datamentioning
confidence: 99%
See 1 more Smart Citation
“…So far, different sources for GWs in the troposphere have been identified, e.g. flow over orography, convection, jets and fronts, as well as secondary generation in the region of GW breaking (Smith, 1979;Gill, 1982;Baines, 1995;Fritts and Alexander, 2003;Sutherland, 2010;Plougonven and Zhang, 2014;Vadas et al, 2003). GWs are propagating from their sources in the troposphere and the tropopause region (Sato et al, 2009;Fritts et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The airborne observations took place during the intensive observing period 6 (IOP 6) on 28 January 2016 in the framework of the combined missions POLSTRACC (The Polar Stratosphere in a Changing Climate), GW-LCYCLE II and SALSA (Seasonality of Air mass transport and origin in the Lowermost Stratosphere using the HALO Aircraft). An overview of the performed HALO research flights can be found in Oelhaf et al (2019). In January 2016, the DLR research aircraft Falcon and HALO operated from the airport of Kiruna (67.82 • N,20.33 • E), northern Sweden, to investigate chemical and dynamical processes 95 in the UTLS region at high latitudes.…”
mentioning
confidence: 99%